Systematic review: better or (otherwise) misleading for clinical decision? - Hardyanto Soebono, Muhammad Bayu Sasongko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Systematic review is a method to combine multiple sources of evidence through an explicit and reproducible way ofliterature search and critical appraisal of the quality of included studies, with or without mathematical methods tosynthesis these information. Since this method was first introduced more than centuries ago, systematic review hasbeen increasingly popular and widely used particularly in the area of medicine. Systematic review is often veryuseful to physicians to help supporting the clinical decision making and significantly reducing their time to seek forappropriate evidence. However, despite its reproducible and systematic steps to substantially minimize the presenceof biases, physicians should still be aware that systematic review is not completely biases resistant. Inclusion ofpoor quality studies, heterogeneity, and publication or other reporting biases are commonly evident in systematicreview that may hinder the quality of the conclusion. This review summarizes the core principals of systematicreview and its potential biases, and discusses when the systematic review is useful or needing careful attention.Key words: treatment-scientific evidence- meta-analysis- critical appraisal-outcomes